Short-Term Energy Consumption Prediction in Korean Residential Buildings Using Optimized Multi-Layer Perceptron - Fazli Wahid; Do Hyeun Kim (Kuwait Journal of Science)
For the designing and management of energy production and storage systems, the prediction of household short-term energy consumption is of vital importance. In this paper, we present the prediction methodology for short-term energy consumption using optimized multi-layer perceptron. A total of 20 models of multi-layer perceptrons with different architectures were developed for hourly energy consumption prediction.  For the determination of best combinations of learning algorithms, hidden layers’ transfer functions and output layer functions, different types of training algorithms and hidden layer and output layer functions were considered. Two main training algorithms namely scaled conjugate gradient, and Levenberg-Marquardt back propagation algorithms were used for training. In the hidden layer, tangent and logarithmic sigmoid equations were used as activation functions and linear, logarithmic sigmoid and tangent sigmoid were used as output functions. The evaluation of performance of models was based on mean absolute error (MAE), mean square error (MSE) and root mean square error (RMSE).The performance and feasibility of the proposed model have been tested on real data of some residential buildings of Seoul, Republic of Korea for a specific period of time. We have total of 14260 (20 Apartments x 31 Days x 23 Hours) samples’ data which was divided into 70% (9982 samples) training and 30% (4278 samples) testing.